They Knew They Were Pilgrims: Plymouth Colony and the Contest for American Liberty - Turner, John G. (Yale University Press, 2020)
An ambitious new history of the Pilgrims and Plymouth Colony, published for the 400th anniversary of the Mayflower's landing.